Cultural Values as Anti-Fraud Strategy: Lessons from Islamic Schools - Setiawan, Nanang; Cholili, Azwar (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
This study investigates the potential of cultural values as anti-fraud strategies in Islamic schools, with a specific focus on institutions in Surabaya. Utilizing a qualitative case study approach, the research gathered data through direct observation and unstructured interviews with informants. The findings underscore the importance of five core cultural values: honesty, trust, mutual cooperation, mutual respect, and mutual care. The study concludes that the implementation of these values is crucial in fostering financial reporting accountability and reducing the risk of fraud within the school environment. These insights can benefit not only educational institutions but also other organizations by providing valuable guidance for developing internal anti-fraud programs based on the internalization of cultural values. By understanding how these values contribute to a trustworthy and ethical internal environment, institutions can proactively anticipate and minimize the potential for fraudulent activity.==============================================================================================================ABSTRAK – Nilai Budaya sebagai Strategi Anti Kecurangan: Kajian dari Sekolah Islam. Penelitian ini bertujuan untuk mengeksplorasi strategi pencegahan kecurangan melalui implementasi nilai-nilai budaya di Sekolah Islam di Surabaya. Penelitian ini bersifat kualitatif melalui metode studi kasus dengan data yang dikumpulkan secara observasi langsung di lokasi penelitian dan wawancara tidak terstruktur dengan sejumlah informan. Hasil kajian menunjukkan bahwa nilai-nilai budaya yang diimplementasikan di sekolah adalah: kejujuran, amanah, gotong royong, saling menghargai, dan saling peduli. Implementasi nilai-nilai budaya tersebut terbukti menjadi faktor utama dalam membentuk akuntabilitas pelaporan keuangan dan mencegah terjadinya kecurangan di lingkungan sekolah. Hasil ini dapat menjadi panduan tidak hanya bagi lembaga pendidikan tetapi juga berbagai organisasi lainnya dalam membangun program pencegahan kecurangan internal dengan internalisasi nilai-nilai budaya tersebut. Pemahaman akan pentingnya nilai-nilai tersebut berkontribusi terhadap meningkatnya kepercayaan dan terciptanya lingkungan internal yang beretos kerja baik sehingga dapat meminimalisir berbagai potensi kecurangan.